Strategi Penyelesaian Pembiayaan Bermasalah (Studi Kasus Pada Bmt Mitra Usaha Ummat Di Sleman) - WARDHANI, SARASWATI (2012)
Any financial institution that provides credit or loans must have a credit risk, one of which is that credit will become problematic. There are many factors that affect the financing problems, among other issues the customer character and economic problems. To solve these financing problems, financial institutions have several ways to solve them, among others, reschedulling, restructuring, reconditioning. This study aims to determine the causes of financing problems and to find financing problem-solving strategies in BMT Mitra Usaha Ummat in Sleman. Informants in this study are the manager and several customers who have financing problems. Determination of informants in this study is done on purpose (purposive sampling). The methods used are interviews, observation and literature study, whereas method of data analysis uses qualitative analysis with in-depth interviews approach and quantitative analysis with ratio analysis. Based on results of the data analysis, then the cause of the bad loans to BMT Mitra Usaha Ummat was due to the economic problems of the customer in which the income derived from an unfixed business, but the biggest factor was the eruption of Merapi making the most businesses of customers declined, bankruptcy and even destroyed. Steps taken by the BMT Mitra Usaha Ummat in addressing the financing problem is to make a persuasive approach to customers who have financing problems and also, by way of rescheduling and restucturing. Especially for customers who were affected the volcano eruption, then waivers, deletions and capital increase were provided. The results of data analysis of the ratio before and after implementation of the strategy were as follows: the result of using the current ratio, liquidity ratioa reached before and after implementation of the strategy were 110.8% and 110%. It means the ratio before and after implementation of the strategy is not good; from the leverage ratios using the Total Debt to Total Assets (TDR) achieved before and after the implementation were 89.8% and 90.5%, it means the ratio before and after implementation of the strategy is good; while those using Total Debt to Equity Ratios (DER) achieved before and after the implementation were 880% and 1080%, it means the ratio before and after implementation of the strategy process is not good. The profitability ratios using the Net Profit Margin (NPM) achieved before and after were 2.9% and 4.6%, it means the ratio before and after implementation of the strategy is efficient; by using the Rate of Return on Total Assets (ROA) reached before and after were 0.04% and 0.07%, it means the ratio before and after implementation of the strategy is less efficient, and the latter, Rate of Return on Net Wort (ROE) reached before and after were 0.4% and 0.8%, it means the ratio before and after implementation of the strategy is not efficient. Based on the above discussion it can be concluded that the factors causing financing problems in BMT Mitra Usaha Ummat, are among the others: the character of the customers and the economic problems. The way conducted the BMT Mitra Usaha Ummat party to resolve the financing problems were: BMT Mitra Usaha Ummat was looking for information about the cause of such problematic financing, BMT Mitra Usaha Ummat provided suggestions for its customers in managing the loan money so that their business can run smoothly and ultimately, customers can pay off their obligation, namely, to repay the credit installments, and BMT Mitra Usaha Ummat party began to take settlement action to resolve the financing problems: First, the BMT party approached its customer who were experiencing financing problems in order to obtain further information and to determine what action should be taken. Further action can be done by using rescedulling or restructuring. Especially for customers who were affected by eruption of Merapi, special treatments were provided for them, namely elimination of financing, principal reduction and margin, and the addition of new financing and provision of business mentoring. From the analysis of financial statements with liquidity ratios, leverage ratios and profitability ratios, it can be seen that the financial condition of BMT Mitra Usaha Ummat before and after implementation of the strategy was not good. Therefore we can conclude that the implemented strategy was less successful.